THE IMPORTANCE OF THE TRANSLITERATION IN TRANSLATION (Innovate Conferences, 2025)
This thesis is on the importance of the transliteration in translation. The present study collects and gives information about the lexical transformation named transliteration that involves with the problems of translating the names of people, geographical names, newspapers and magazines, enterprises, organizations, as well as hotel names. And as an example, it gives opinions of some linguists about the transliteration and starts with an analysis of this lexical transformation with the examples which are taken from the translation versions of “Oʻtkan kunlar”.